A complicated case of atypical hemolytic uremic syndrome with frequent relapses under eculizumab - Schalk, Gesa; Kirschfink, Michael; Wehling, Cyrill; Gastoldi, Sara; Bergmann, Carsten; Hoppe, Bernd; Weber, Lutz T. (Pediatric nephrology, 2015)
Atypical hemolytic uremic syndrome (aHUS) is a form of thrombotic microangiopathy characterized by uncontrolled activation of the alternative complement pathway with consecutive generation of the terminal complement complex. Mortality is increased, particularly in the first year of the disease. Therapeutic options include plasma therapy and terminal complement blockade using the anti-C5 monoclonal antibody eculizumab. Eculizumab prevents activation of the terminal sequence of the complement cascade and formation of the potentially lytic terminal complement complex (C5b-9).
Gesehen am 17.06.2020